NEW OPPORTUNITIES OF MONOTHERAPY WITH NEBILET FOR PATIENTS WITH CORONARY HEART DISEASE AND ARTERIAL HYPERTENSION - V. M. Loyfman; A. B. Ostrovsky; Z. P. Zhirnova; L. G. Horuk (Российский кардиологический журнал)
Nebilet – is a new β-adrenoceptor blocking agent possessing both superseleсtive and NO-producing properties. Efficacy and safety of nebilet monotherapy of 5 mg/d were evaluated for 20 patients with mild and moderate essential hypertension during 8 weeks of treatment. Positive hypotensive effect was achieved in 79% of patients, average daily level of systolic and diastolic pressure decreased from 144,1±2,5 to 132,5±3,4 mm Hg and from 88,8±1,5 to 79,5±2,3 mm Hg respectively. A marked diminishing (by 80 %) of painful and painless myocardial ischemia overall duration was also observed.We didn’t reveal the inhibition of inotropic action, whereas good influencies to the remodelling of myocardium have oсcured. There were no serious adverse effects and laboratory deviations during the therapy.